2019
DOI: 10.1128/jcm.01645-19
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Human Immunodeficiency Virus Infection by Use of a Fourth-Generation Antigen/Antibody Assay and Dried Blood Spots: In-Depth Analysis of Sensitivity and Performance Assessment in a Cross-Sectional Study

Abstract: We evaluated the performance of a fourth-generation antigen/antibody (Ag/Ab) assay for detecting HIV-1 infection on dried blood spots (DBS) both in a conventional laboratory environment and in an epidemiological survey corresponding to a real-life situation. Although a 2-log loss of sensitivity compared to that with plasma was observed when using DBS in an analytical analysis, the median delay of positivity between DBS and crude serum during the early phase postacute infection was 7 days. The performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…Thirty-two (89%) reported the methodology used to elute the DBS samples [14,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][35][36][37][39][40][41][42][44][45][46][47][48][49][50][51][52]. The shortest incubation period of the DBS in elution buffer (50 μl 0.05% PBS/Tween-20) was 30 minutes [42] and the longest incubation period of the DBS in elution buffer (700 μl and 300 μl PBS/0.05% BSA) was 18-24 hours [17]) ( Table 2).…”
Section: Elution Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty-two (89%) reported the methodology used to elute the DBS samples [14,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][35][36][37][39][40][41][42][44][45][46][47][48][49][50][51][52]. The shortest incubation period of the DBS in elution buffer (50 μl 0.05% PBS/Tween-20) was 30 minutes [42] and the longest incubation period of the DBS in elution buffer (700 μl and 300 μl PBS/0.05% BSA) was 18-24 hours [17]) ( Table 2).…”
Section: Elution Methodsmentioning
confidence: 99%
“…Overall, DBS and serum samples from 16,255 individuals were included: 13,742 (84.5%) adults, 560 (3.4%) 5-to 17-year old's and 2,082 (12.8%) less than five years old. Two studies reported antibodies against hepatitis A [14,15], nine hepatitis B [16][17][18][26][27][28]46,48,51], ten hepatitis C [19][20][21][22][26][27][28]37,46,48], eight HIV [23][24][25][26][27][28]46,50], three human papillomavirus (HPV) [29,30,37], three measles [31,32,42], three rubella [33,34,42], two syphilis [40,46], two H. pylori [35,47] and two malaria [38,49]. Twelve papers reported on Chagas disease [35], Epstein-Barr virus [36], HPV, H. pylori, hepatitis C and polyomavirus [37], Strong...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The US Department of Transportation and US Postal Service consider DBS to be nonregulated and exempt materials for shipping if they are properly packaged [ 15 ], making it easy to return DBS specimens from a clinic or home directly to a high complexity clinical laboratory for testing. Prior studies have successfully used DBS to detect antibodies against Epstein–Barr [ 16 ], Rabies [ 17 ], Hepatitis B and C [ 18–20 ], HIV [ 18 , 21 , 22 ], Herpes Simplex [ 23 ] and Ebola [ 24 ] viruses.…”
mentioning
confidence: 99%